PENGEMBANGAN KOORDINASI ATS MESSAGE ANTARA UNIT BASE OPERATION LANUD HASANUDDIN DENGAN UNIT ATSRO DI MAKASSAR AIR TRAFFIC SERVICE CENTER (MATSC) - Intan Puspita Sari; Fatmawati; Yuni Saptandari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Air Traffic Service Reporting Office (ATSRO) unit is one of the units located at the Makassar Air Traffic Service Center (MATSC) which records for managing flight plans and ATS messages such as delays, changes, departures, arrivals and cancellations as well as validating, verifying and distributing flight plan to the ATS address of the relevant unit. On military flights, the flight plan is sent by the Base Operations Unit to ATSRO to be validated by the ACO (Aeronautical Communication Officer) then the flight plan is distributed to the related ATS units. However, there are several obstacles in the form of the absence of information from the Hasanuddin Airbase Base Operations Unit regarding delays or changes in message of military aircraft flight plans and frequent miss communication between the two parties regarding confirmation of military aircraft flight plans due to the use of personal cell phone numbers of each Operation Base personnel. This affects ACO in sending ATS news which has an impact on the effectiveness and efficiency of flight services. In this study, the author uses a gap analysis research method, which is to analyze what steps need to be taken to move from the current condition to the desired condition in the future. The results of this study are expected to provide alternative solutions to problems so that coordination between the Lanud Hasanuddin Base Operation Unit and the ATSRO Unit can be well established and improve flight service efficiency.